Neuroglial coupling and the cerebral metabolism of monocarboxylates as detected by 13C nuclear magnetic resonance - Rodrigues, Tiago Brandão (2007)
Tese de doutoramento em Bioquímica (Biofísica Molecular) apresentada à Fac. de Ciências e Tecnologia de Coimbra